O que é arte? O sistema da arte e os livros de artista - Amir Brito Cadôr (2020)
The article addresses an exhibition held at the UFMG library in 2019, bringing together books that have artistic practice and art history as their theme. The art system is highlighted (and questioned) in this set of works, ranging from exhibition invitations and the publication of official opening speeches to a fictional interview by a young artist with one of the most renowned curators today. Art and its various agents are presented based on the examples brought by the artist’s books, which present issues related to contemporary art, such as institutional criticism.